2016
DOI: 10.1371/journal.pone.0147840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3′UTR RET Variants on RET mRNA Secondary Structure and Disease Presentation in Medullary Thyroid Carcinoma

Abstract: BackgroundThe RET S836S variant has been associated with early onset and increased risk for metastatic disease in medullary thyroid carcinoma (MTC). However, the mechanism by which this variant modulates MTC pathogenesis is still open to discuss. Of interest, strong linkage disequilibrium (LD) between RET S836S and 3'UTR variants has been reported in Hirschsprung's disease patients.ObjectiveTo evaluate the frequency of the RET 3’UTR variants (rs76759170 and rs3026785) in MTC patients and to determine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Calcitonin is the most important MTC marker, as it is useful for diagnosis, surgical planning, follow-up, and prognosis. When compared to FNA biopsy for MTC diagnosis, calcitonin presents higher sensibility (nearly 100%) and specificity (95%) (Bugalho et al 2005). High levels of calcitonin may also occur in other medical conditions such as chronic kidney failure, hyperparathyroidism, neuroendocrine neoplasms, lung and prostate tumors and autoimmune thyroiditis (Karanikas et al 2004, Rosario & Calsolari 2016.…”
Section: Diagnosis and Prognostic Markersmentioning
confidence: 99%
“…Calcitonin is the most important MTC marker, as it is useful for diagnosis, surgical planning, follow-up, and prognosis. When compared to FNA biopsy for MTC diagnosis, calcitonin presents higher sensibility (nearly 100%) and specificity (95%) (Bugalho et al 2005). High levels of calcitonin may also occur in other medical conditions such as chronic kidney failure, hyperparathyroidism, neuroendocrine neoplasms, lung and prostate tumors and autoimmune thyroiditis (Karanikas et al 2004, Rosario & Calsolari 2016.…”
Section: Diagnosis and Prognostic Markersmentioning
confidence: 99%
“…Furthermore, the polymorphisms rs7799039 and rs1137101 increase the risk of DTC development, though they do not correlate with tumor aggressiveness [ 16 ]. As another example, supporting evidence of functional relevance was presented by Ceolin and collaborators [ 19 ], who evaluated the frequency of RET (REarranged during Transfection) proto-oncogene 3’UTR variants (rs76759170 and rs3026785) in Medullary Thyroid Carcinoma (MTC) patients. In silico analysis indicated that these variants might affect the secondary structure of RET mRNA, suggesting that they might play a role in the posttranscriptional control of RET transcripts.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, a growing number of studies have identified several SNPs associated with TC risk [ 10 – 17 , 19 , 20 , 22 , 46 49 ]. In the study by Gudmundsson and collaborators [ 46 ], a GWAS analysis was performed in a population from Iceland and showed a strong association of SNPs rs965513 and rs944289 with papillary and follicular thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies showed an additive effect of the described polymorphic variants on the risk of developing an aggressive MTC. In their last report, Ceolin et al (2016) have shown that the c.2508C>T variant is in a strong LD with RET 3′UTR variants. They also performed an in silico analysis, which indicated that 3′UTR variants may affect the secondary structure of RET mRNA and posttranscriptional processing.…”
Section: Discussionmentioning
confidence: 99%
“…Da Silva et al (2003) have described various MTC clinical courses in a multigeneration family and suggested a possible effect of singlenucleotide polymorphisms (SNPs) in the RET gene on the heterogeneous clinical course of the familial MTC. Some other reports have shown that RET genetic variants may be associated with a higher risk of aggressive early-onset sporadic MTC (sMTC) (Gimm et al 1999, Ruiz et al 2001, Berard et al 2004, Elisei et al 2004, Baumgartner-Parzer et al 2005, Siqueira et al 2010, Ceolin et al 2016. Recent studies by Ceolin et al (2016) have shown a significant correlation between polymorphisms in the 3′UTR region and the secondary structure of the RET mRNA, suggesting their role in posttranscriptional control of the RET transcripts and disease presentation in MTC patients.…”
Section: Introductionmentioning
confidence: 99%